2009
DOI: 10.1016/j.disc.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

On the representability of totally unimodular matrices on bidirected graphs

Abstract: a b s t r a c tWe present a polynomial time algorithm to construct a bidirected graph for any totally unimodular matrix B by finding node-edge incidence matrices Q and S such that QB = S.Seymour's famous decomposition theorem for regular matroids states that any totally unimodular (TU) matrix can be constructed through a series of composition operations called k-sums starting from network matrices and their transposes and two compact representation matrices B 1 , B 2 of a certain ten element matroid. Given tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Seymour has shown in [13] that network matrices and their transposes are the main building blocks for TU matrices. Moreover, in [11], it has been shown that the building blocks of TU matrices are matrices associated with bidirected graphs. In this paper we focus on SU matrices which stand between the classes of network and TU matrices and show the network structure of that class.…”
Section: Network and Unimodular Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seymour has shown in [13] that network matrices and their transposes are the main building blocks for TU matrices. Moreover, in [11], it has been shown that the building blocks of TU matrices are matrices associated with bidirected graphs. In this paper we focus on SU matrices which stand between the classes of network and TU matrices and show the network structure of that class.…”
Section: Network and Unimodular Matricesmentioning
confidence: 99%
“…where, in the ⊕ Network matrices and TU matrices are known to be closed under these operations (see [11] and [12], respectively). These operations have been originally defined in the more general framework of regular matroids in [13] and here we present the special form of these operations as they applied to the compact representation matrices in R, i.e.…”
Section: A K-sum Decomposition Of Strongly Unimodular Matricesmentioning
confidence: 99%
“…Various problems, such as capacitated nonsimple b-matchings, in which 1-matchings and simple b-matchings are included, capacitated b-edge covers, and minimum cost flows, are given a single unified formulation as an optimization problem over bidirected graphs. Bidirected graphs have also gained attention in the studies of nowhere-zero integral flows [1,4,22] and totally unimodular matrices [2,20]. Needless to say, numerous studies exist regarding digraphs and signed graphs; see, e.g., Schrijver [21] or Zaslavsky [23].…”
mentioning
confidence: 99%